Closed-Eye Visualizations in the Setting of Hyponatremia - Travis Peck; Christopher Mercogliano; Eugene York (Case Reports in Medicine)
Purpose. To report a case of closed-eye visualizations and to clarify the different types of hallucinations and their etiologies. Methods. Retrospective case report of a patient with closed-eye visualizations secondary to hyponatremia. Clinical findings, physical exam, laboratory assessment, treatment, and disease course from the patient’s hospitalization were used in creating this report. Follow-up data after discharge were also obtained. Results. Closed-eye visualizations were diagnosed as secondary to hyponatremia, as they did not occur with the eyes open, and potential alternate causes were excluded. Serum sodium nadir was 119 mEq/L. Symptoms resolved with correction of hyponatremia via fluid resuscitation and electrolyte replenishment. There has been no recurrence of the symptoms. Conclusion. This patient had hallucinations exclusively with the eyes closed, which must be differentiated from the release hallucinations seen with the eyes open in Charles Bonnet syndrome. This patient had no visual loss or retinal disease, which should be suspected in open eye hallucinations.